Fatty acid and lipophilic vitamin composition of seaweeds from Antalya and Canakkale (Turkey) - Caf, F.; Sen Ozdemir, N.; Yilmaz, O.; Durucan, F.; Ak, I (Consejo Superior Investigaciones Cientificas-Csic, 2019)
The lipophilic vitamin and fatty acid profiles were determined in five edible seaweeds: Corallina elongata J. Ellis & Solander, 1786; Cystoseira barbata (Stackhouse) C. Agardh, 1820; Jania rubens (Linnaeus) J.V. Lamouroux, 1816; Laurencia obtusa (Hudson) J.V. Lamouroux, 1813 and Sargassum vulgare C. Agardh, 1820. Saturated fatty acids (SFAs) were the major fatty acid group, and 16:0 formed the highest SFA content (34-40%). 16: 0 was higher in the brown seaweeds (C. barbata, 40.55%; S. vulgare, 37.11%) than in the red seaweeds (C. elongata, 36.5%; L. obtusa, 34.57%; J. rubens, 34.22%). The other major fatty acids in the seaweeds were 18: 1n-9 and 16: 1n-7 from MUFA in the analyzed species. In addition, EPA was found in significant levels in the red seaweeds, whereas DHA was not detected in the analyzed species. The findings showed that difference among species were not statistically significant (p = 0.09-0.11), yet differences between two families (Sargassaceae and Corallinaceae) were significant (p = 0.006) in the fatty acid profile (p < 0.01). Also, differences between the Corallinaceae and Rhomomelaceae families were partially significant (p = 0.011-0.013) (p < 0.01). K1 and K2 vitamins as well as delta-tocopherol, alpha-tocopherol and retinol acetate were determined to be present in the seaweed extracts. Finally, ergosterol, stigmasterol and beta-sitosterol were found in all samples in differing ratios per species.
Keywords: alpha-tocopherol; Edible seaweeds; Fatty acid; Lipophilic vitamin